2006
DOI: 10.1021/es052205j
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the Effect of Soil Moisture on the Aerobic Microbial Mineralization of Selected Pesticides in Different Soils

Abstract: A standardized quantitative approach was developed to reliably elucidate the effect of increasing soil moisture on pesticide mineralization. The mineralization of three aerobically degradable and chemically different 14C-labeled pesticides (isoproturon, benazolin-ethyl, and glyphosate) was studied under controlled conditions in the laboratory at an identical soil density of 1.3 g cm(-3). The agricultural soils used are characterized by (i) large variations in soil texture (sand content 4-88%) and organic matte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(80 citation statements)
references
References 25 publications
6
71
1
1
Order By: Relevance
“…Multivariate regression was attempted; however, the fit of the univariate models could not be improved by addition of the other parameters measured in this study (data not shown). Many microbial activities are known to increase with soil moisture (15,21,42); however, microbial community structure responses to moisture are less clear. Some studies have found shifts in soil microbial community composition under different moisture regimens (11,15), while others have reported no relationship with soil moisture changes (3,29).…”
Section: Vol 77 2011mentioning
confidence: 99%
“…Multivariate regression was attempted; however, the fit of the univariate models could not be improved by addition of the other parameters measured in this study (data not shown). Many microbial activities are known to increase with soil moisture (15,21,42); however, microbial community structure responses to moisture are less clear. Some studies have found shifts in soil microbial community composition under different moisture regimens (11,15), while others have reported no relationship with soil moisture changes (3,29).…”
Section: Vol 77 2011mentioning
confidence: 99%
“…that affect the microbial activity as well as diffusion of the chemicals in the soil. The effect of soil moisture on the aerobic microbial mineralization of the selected pesticides was quantified by Schroll et al, (2006). They found a linear relation between the soil moisture and relative pesticide mineralization.…”
Section: Soil Conditionsmentioning
confidence: 99%
“…Schroll et al [18], Alberty [19], Guillot et al [20], Mastronicolis et al [21], Singh et al [22] are responsible for changes in microbial diversity and for expanded numbers and metabolic activities of microorganisms in the rhizosphere microenvironment, this phenomenon called the rhizosphere effect [10,15,17,23]. Many studies have investigated the effects of soil moisture, temperature, aeration, pH, and organic matter content on the biodegradation of pesticides [11,24].…”
Section: Factors Affecting Rhizoremediationmentioning
confidence: 99%